The diagnosis of mineral deficiences in plants - By visual symptoms - A colour atlas and guide - Wallace, T. (Londres Stationery Office, 1951)
Lab.de Fisiologia Vegetal
Donacion Ing. Agr. A. Speroni
Keywords: Fisiología